The Bunyans - Wood, Audrey; Shannon, David, 1959- (New York : Blue Sky Press, 1996)
Paul Bunyan, his wife, and their children do some ordinary things which result in the formation of Niagara Falls, Bryce Canyon, and other natural monuments.
School Library Journal starred
Pub Weekly
Booklist
3.9
K-3
Keywords: Bunyan, Paul (Legendary character) -- Juvenile fiction; Bunyan, Paul (Legendary character) -- Fiction; Tall tales; Natural monuments -- Fiction; National parks and reserves -- Fiction; Bunyan, Paul (Legendary character) -- Fiction; Tall tales; Natural monuments -- Fiction; National parks and reserves -- Fiction